Maternal Functioning and Depression Scores Improve Significantly With Participation in Visiting Moms® Program. (January 2021) - Barkin, Jennifer L.; Beals, Laura; Bridges, Christy C.; Ezeamama, Amara; Serati, Marta; Buoli, Massimiliano; Erickson, Amber; Chapman, Megan; Bloch, Joan R.
BACKGROUND: Postpartum depression is the most common complication of childbearing can affect the entire family unit. Health professionals must strive to identify and develop effective, feasible solutions for women during this critical period.AIMS: To determine whether postpartum maternal functioning (as measured by the Barkin Index of Maternal Functioning) and depression symptoms (as measured by the Patient Health Questionnaire-9) were improved after participation in the Visiting Moms program.METHOD: Paired data were collected from women at program intake and after completion of the Visiting Moms program. Visiting Moms provides services through eastern and central Massachusetts and was designed to support new mothers throughout the infant's first year of life. The study population was composed of adult women living in the Jewish Family and Children's Services geographic catchment area, who enrolled in Visiting Moms between January 1, 2013, and December 31, 2015. Descriptive statistics were calculated for all 402 women enrolled in this timeframe. Utilizing a pretest/posttest design, paired t tests were performed for the Barkin Index of Maternal Functioning ( n = 149) and for the Patient Health Questionnaire-9 ( n = 156), where women had complete scores at both intake and completion, to determine the program's potential impact on depressive symptoms and functional status.RESULTS: Functioning and depression scores were significantly improved after participation in the program.CONCLUSIONS: Visiting moms, and similar programs, aimed at delivery of enhanced social support, may be effective in promoting mental and emotional wellness among new mothers who are require additional support in the postpartum period.